2021
DOI: 10.1186/s40249-021-00859-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of conventional and non-invasive diagnostic tools for detecting Plasmodium falciparum infection in southwestern Cameroon: a cross-sectional study

Abstract: Background Malaria remains a significant health challenge in sub-Saharan Africa, with early diagnosis critical to reducing its morbidity and mortality. Despite the increasing Plasmodium spp. diagnostic capabilities, access to testing is limited in some cases by the almost absolute requirement for blood from potentially infected subjects as the only sample source for all conventional methods. A rapid test on non-invasive specimen with comparable performance to microscopy for the screening or dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 59 publications
2
3
0
Order By: Relevance
“…The results from some studies (Agaba et al, 2022, Apinjoh et al, 2021, Abuaku et al, 2021b, Bwire et al, 2019 agree with our study results. These studies also concentrated on using mRDTs to identify malaria.…”
Section: Sociodemographic Characteristics Of the Participantssupporting
confidence: 91%
“…The results from some studies (Agaba et al, 2022, Apinjoh et al, 2021, Abuaku et al, 2021b, Bwire et al, 2019 agree with our study results. These studies also concentrated on using mRDTs to identify malaria.…”
Section: Sociodemographic Characteristics Of the Participantssupporting
confidence: 91%
“…The results from some studies agree with our study results [19,[23][24][25]. These studies also concentrated on using mRDTs to identify malaria.…”
Section: The Most Common Plasmodium Speciessupporting
confidence: 90%
“…The same study also showed the limit of parasite detection of 63,150 parasites/μL for urine and 57,335 parasites/μL for saliva, as well as a significant correlation between detection rates and parasite densities. However, another study with a greatly lower parasitemia range of 105 to 7200 parasites/μL used the same RDT but was able to achieve higher sensitivities of ~70% for urine and saliva relative to results of microscopy and blood PCR [ 4 ]. Rather than 100%, the study only obtained specificities of 77.1% to 93.1% for Pf detection in urine and saliva samples.…”
Section: Antigen-based Diagnostic Methodsmentioning
confidence: 99%
“…The main challenge of RDTs is their limitation to detect infections at low parasitemia [ 4 ]. WHO has set the lowest level of detection to 200 parasites/µL of blood for field tests [ 66 ].…”
Section: Antigen-based Diagnostic Methodsmentioning
confidence: 99%
See 1 more Smart Citation